Association between energy drink consumption, depression and suicide ideation in Korean adolescents. (June 2020) - Kim, Hun; Park, Junha; Lee, Seungryul; Lee, Sang Ah; Park, Eun-Cheol
Background: Suicide is the leading cause of death among adolescents in South Korea. Negative influences of the abuse of energy drinks on mental health problems have emerged. Aims: This study aimed to analyze the relationship between energy drink consumption, depression and suicide ideation. Methods: We analyzed the data of 26, 346 boys and 26, 966 girls who participated in the 2015 Korean Youth Risk Behavior Web-Based Survey. The independent variable was the frequency of energy drink consumption per week. Experience of depression and suicide ideation were considered as the dependent variables. Multiple logistic regression was performed. Results: An association was found between energy drink intake per week and depressive mood. Moreover, the most frequent energy drink intake (three times or more per week) group showed the highest association with depressive mood (odds ratios (ORs); boys: ORs = 1.40, 95% confidence interval (CI): 1.25–1.56; girls: ORs = 1.61, 95% CI: 1.44–1.79) and suicide ideation (boys: ORs = 1.46, 95% CI: 1.27–1.69; girls: ORs = 1.36, 95% CI: 1.20–1.55). Conclusion: We observed that consumption of excessive amounts of energy drinks is associated with depression and suicide ideation. Therefore, appropriate regulation or education is needed to prevent adolescents from experiencing adverse outcomes.